Characterizing mitochondrial phenotypes and MERCS in aged human skeletal muscle myoblasts - Yufu Unten; Kazuaki Takafuji; Yumiko Masukagami; Isshin Shiiba; Keigo Horiuchi; Filip Husnik; Shigeru Yanagi; Norifumi Tateishi; Toshihide Suzuki (PLoS ONE, 2026)
Age-associated declines in skeletal muscle function are linked to cellular senescence and mitochondrial alterations, yet mitochondrial phenotypes in aged human myoblasts remain insufficiently characterized. Here, we examined primary skeletal muscle myoblasts from young and elderly donors to assess mitochondrial function, morphology, and mitochondria–endoplasmic reticulum (ER) contact sites (MERCS). Myoblasts from older donors exhibited senescence features, including elevated SA-β-gal activity and reduced Lamin B1 expression, accompanied by increased mitochondrial oxidative stress. Despite marked mitochondrial hyperfusion and increased mitochondrial DNA content, mitochondrial oxygen consumption rate and membrane potential per mitochondrial area were comparable between young and old cells. MERCS were significantly elevated in aged myoblasts and were reduced by scavenging mitochondrial reactive oxygen species (mtROS), indicating an association between oxidative stress and MERCS formation. These findings suggest that mitochondrial hyperfusion and enhanced MERCS accompany cellular aging in human myoblasts and may contribute to maintaining mitochondrial function under elevated oxidative stress.